A hybrid physical–chemical deposition process at ultra-low temperatures for high-performance perovskite solar cells1. Issue 23 (21st June 2015) - Peng, Yanke; Jing, Gaoshan; Cui, Tianhong
<x xml:space="preserve">Abstract</x> The quality of a perovskite film will directly determine the performance and stability of the corresponding perovskite solar cell.